Statistical combination of ATLAS Run 2 searches for charginos and neutralinos at the LHC - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sauer, Christof; Schöning, André; Schultz-Coulon, Hans-Christian; et al. (Physical review letters, 2024)
Statistical combinations of searches for charginos and neutralinos using various decay channels are performed using 139 fb−1 of 𝑝⁢𝑝 collision data at √𝑠 =13 TeV with the ATLAS detector at the Large Hadron Collider. Searches targeting pure-wino chargino pair production, pure-wino chargino-neutralino production, or Higgsino production decaying via standard model 𝑊, 𝑍, or ℎ bosons are combined to extend the mass reach to the produced supersymmetric particles by 30-100 GeV. The depth of the sensitivity of the original searches is also improved by the combinations, lowering the 95% C.L. cross-section upper limits by 15%-40%.
Gesehen am 30.04.2025
The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, D.F. Rassloff, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, M. Wessels, J. Zinsser [und 2932 weitere]